CD15 Expression Does Not Identify a Phenotypically or Genetically Distinct Glioblastoma Population. (27th May 2015) - Kenney-Herbert, Emma; Al-Mayhani, Talal; Piccirillo, Sara G.M.; Fowler, Joanna; Spiteri, Inmaculada; Jones, Philip; Watts, Colin
Abstract: : Recent research has focused on the hypothesis that the growth and regeneration of glioblastoma (GB) is sustained by a subpopulation of self-renewing stem-like cells. This has led to the prediction that molecular markers for cancer stem cells in GB may provide a treatment target. One candidate marker is CD15: we wanted to determine if CD15 represented a credible stem cell marker in GB. We first demonstrated that CD15-positive (CD15+) cells were less proliferative than their CD15-negative (CD15−) counterparts in 10 patient GB tumors. Next we compared the proliferative activity of CD15+ and CD15− cells in vitro using tumor-initiating primary GB cell lines (TICs) and found no difference in proliferative behavior. Furthermore, TICs sorted for CD15+ and CD15− were not significantly different cytogenetically or in terms of gene expression profile. Sorted single CD15+ and CD15− cells were equally capable of reconstituting a heterogeneous population containing both CD15+ and CD15− cells over time, and both CD15+ and CD15− cells were able to generate tumors in vivo. No difference was found in the phenotypic or genomic behavior of CD15+ cells compared with CD15− cells from the same patient. Moreover, we found that in vitro, cells were able to interconvert between the CD15+ and CD15− states. Our data challenge the utility of CD15 as a cancer stem cell marker. Significance: The data from this study contribute to the ongoing debate about the role of cancer stem cells in gliomagenesis. Results showed that CD15, a marker previously thought to be a cancer stem-like marker in glioblastoma, could not isolate a phenotypically or genetically distinct population. Moreover, isolated CD15-positive and -negative cells were able to generate mixed populations of glioblastoma cells in vitro. Abstract : The data from this study contribute to the ongoing debate about the role of cancer stem cells in gliomagenesis. Results showed that CD15, a marker previously thought to be a cancer stem-like marker in glioblastoma, could not isolate a phenotypically or genetically distinct population. Moreover, isolated CD15-positive and -negative cells were able to generate mixed populations of glioblastoma cells in vitro.